Effect of differences in residual feed intake on gastrointestinal microbiota of Dexin fine-wool meat sheep - Wang, Ziting; Wu, Weiwei; Lv, Xuefeng; Xing, Weiting; Wang, Xu; Tuo, Yong; Ma, Yan; He, Linjiao; Zhang, Zhijun; Zheng, Wenxin (Frontiers in Microbiology, 2024)
In this study, we examined the effects of different residual feed intakes (RFIs) on nutrient digestibility and the microbiota of the digestive tract of Dexin fine-wool sheep. Fifty 70-day-old Dexin fine-wool meat lambs were selected as the experimental group and fed in a single pen for 100 days. Based on their mid-term metabolic weight, 100-day average daily weight gain and daily feed intake, the male Dexin lambs were divided into a low-RFI group (13), a mid-RFI group (18), and a high-RFI group (11). Six male Dexin lambs were selected from each group to collect feces, rumen digesta and solid digesta. Rectal feces were collected from three lambs in each group. The results showed that the digestibility of dry matter and crude protein by sheep in the L-RFI group was than that in the H-RFI group (P < 0.05). Within the microbial population, f_Anaerovoracaceae, g_Christensenellaceae_R_7_group, p_Proteobacteria, and g_Roseburia were significantly correlated with RFI. Energy metabolism, metabolism of amino acids and carbohydrates, transport and catabolism, and cell migration pathways were upregulated in the L-RFI group. The differences in the microbiota of the digestive tract of sheep with different RFIs were reflected in the presence of some key bacterial genera rather than changes in the overall microbial diversity.